In Vitro Mutation Induction of Chrysanthemum (Chrysanthemum morifolium) Maruta Variety for Lowlands Using EMS (Ethyl Methane Sulfonate) - Abigail Febby Puspo Harijono; Sukendah; Pangesti Nugrahani; Ragapadmi Purnamaningsih (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Chrysanthemums (Chrysanthemum morifolium) are among the most popular ornamental plants due to their diverse types, shapes, and colors, making them highly valued in the horticultural market. In Indonesia, chrysanthemums are typically grown in highland regions, where production and flower quality are declining due to global temperature changes. To sustain production, new varieties adapted to lowland conditions are required. This study aimed to induce mutations in the Maruta chrysanthemum variety using Ethyl Methane Sulfonate (EMS) to enhance adaptability and biodiversity. Explants were treated in vitro with EMS concentrations of 1%, 1.5%, and 2%. Quantitative traits—including survival percentage, explant height, number of shoots, leaves, and roots—were analyzed using ANOVA and Tukey's test at the 5% level. Qualitative traits, such as stem and leaf color, were assessed using the Munsell Color Chart. Results showed that more than 50% of Maruta explants survived under all treatments. However, explant height, number of leaves, and number of roots decreased as EMS concentration increased, compared with the control.